FAMILY CECIDOMYIIDAE - Maia, Valéria Cid (Zootaxa, 2016)
This large family is poorly known in Colombia, where only 44 species have been recorded in 20 genera. All of them are included in Cecidomyiinae, which is the most diverse subfamily of gall midges in number of species and feeding habits, including phytophagous, predaceous and fungivorous species. Most of them are galler. The other subfamilies have never been recorded in this country.